2016
DOI: 10.1177/0886260516632355
|View full text |Cite
|
Sign up to set email alerts
|

Racial Composition of Couples in Battered Spouse Syndrome Cases: A Look at Juror Perceptions and Decisions

Abstract: This study manipulated the race of the defendant (wife) and the victim (husband)-White/White, White/Black, Black/Black, and Black/White-in a murder case involving a history of intimate partner violence (IPV) to examine the potential prejudicial impact of race on juror decision-making. A total of 244 jury-eligible American community members read a trial transcript of a murder case in which the defendant claimed self-defense using evidence of battered spouse syndrome. Participants provided a verdict, responsibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…In summary, participants rate the situations according to stereotypical gender roles and thus show more concern for the female than the male victims, and consider violent situations with male perpetrators more severe than violent situations with female perpetrators (Hammock et al, 2017;Russell et al, 2016;Scarduzio et al, 2017). The results were also consistent with studies where mock juries were asked to judge cases of IPV, in which the jurors were more keen on a guilty verdict when the perpetrator was male and the victim female (Mossière et al, 2018;Stanziani et al, 2018). It has been suggested that a reason for this is the perpetrator's ability to arouse fear of injury in the victim, which affects how the severity of the situation is perceived.…”
Section: Perceptual Differences and Communication Of Ipvsupporting
confidence: 77%
See 1 more Smart Citation
“…In summary, participants rate the situations according to stereotypical gender roles and thus show more concern for the female than the male victims, and consider violent situations with male perpetrators more severe than violent situations with female perpetrators (Hammock et al, 2017;Russell et al, 2016;Scarduzio et al, 2017). The results were also consistent with studies where mock juries were asked to judge cases of IPV, in which the jurors were more keen on a guilty verdict when the perpetrator was male and the victim female (Mossière et al, 2018;Stanziani et al, 2018). It has been suggested that a reason for this is the perpetrator's ability to arouse fear of injury in the victim, which affects how the severity of the situation is perceived.…”
Section: Perceptual Differences and Communication Of Ipvsupporting
confidence: 77%
“…Several factors may contribute to the above-mentioned perceptual differences in calibration, accuracy and gender, which might affect the legal process and potentially the verdict. These include offenders' potentially skewed narrative depending on the offender's gender (Hammock et al, 2017;Russell et al, 2016;Savage et al, 2017;Sylaska & Walters, 2014) and the gender of the recipient of the narrative such as law enforcement officials, jury members, or judges (Alfredsson et al, 2016;Berkel et al, 2004;Gover et al, 2011;Hine & Murphy, 2017;Mossière et al, 2018;Strömwall et al, 2014).…”
Section: The Current Studymentioning
confidence: 99%
“…Research suggests the importance of examining the joint effects of age, gender, and race on sentencing outcomes—sentencing is particularly harsh when defendants are young males who are Black or Hispanic (Doerner & Demuth, 2010). Mossière et al’s (2018) findings point to the importance of examining race in the context of a battered spouse syndrome case. Specifically, defendant race (but not the couple’s racial composition) mattered, with jurors rating the male victim as more responsible than the female defendant for the crime when the defendant was Black (vs. White).…”
Section: Discussionmentioning
confidence: 94%
“…The VR videos are shot 10 Previous experimental research that investigated the impact of defendant characteristics such as race and mental illness on trial verdicts provided mock trial transcripts to be read by the evaluators. The race of the victim or defendant is manipulated using photographs and names (Mossiere, Maeder and Pica 2018;Maeder, Mossiere and Cheung 2012), or evaluators were given vignettes that described the offender and the circumstances of the case (Mercado, Bornstein and Schopp 2006). Some studies showed videos of mock trials where the trial conditions, such as eyewitness evidence, has been manipulated by the experimenters (Jones et al 2017).…”
Section: General Idea and The Contribution Of The Papermentioning
confidence: 99%